MENGKAJI PERBEDAAN ANTARA BAHASA MANUSIA DAN ALAT KOMUNIKASI HEWAN - Alya Yulieta; Nicky Tri Handayani; Sukma Arum Sari; Eko Kuntarto; Muhammad Sholeh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
All humans can use language to speak and interact with others to fulfill their life needs. Language also distinguishes humans from other creatures created by God. In contrast, animal communication is limited to instinctive signals used for basic purposes such as warnings, mating, and defending territory. Communication with animals is well established and has not undergone major developments in terms of complexity or well-being. In addition, human language is productive, able to form new sentences and convey ideas that have never been expressed before, while animal communication is limited to repetitive and established behavioral patterns. This article examines the linguistic, biological evolutionary, and cognitive differences that underlie the differences between the two communication systems, and shows that human language explains how this is possible about the unique position of humans in the use of language and the use of animal language.